Ianua linguarum: From Roboredo (1619) to Comenius (1631) - Leite, Marli Quadros; Siqueira, Cínthia Cardoso de (Revista da ABRALIN, 2021)
The purpose of this article is to offer some considerations on the didactic and pedagogical thought of two important figures in seventeenth-century language instruction: the Portuguese grammarian Amaro de Roboredo ( 1580‒165?) and the Moravian educator Jan Amos Comenius (1592‒1670), in order to show how a broad horizon of retrospection of knowledge constituted at that time was decisive in enabling these authors to work on common topics despite their physical distance from one another. The object of this study is the method of language instruction defended by both authors based on the work Ianua linguarum (1611) by Irish priests of Salamanca, probably authored by William Bathe. To this end, we propose treating certain aspects of the horizon of retrospection specific to these authors to situate them in their own time and space as well as to identify the main ideas in language instruction revealed in the following works: Methodo grammatical para todas as linguas (1619) and Porta de linguas ou modo muito acommodado para as entender (1623) by Roboredo as well as Ianua linguarum reserata (1631) and Didactica magna (1657) by Comenius. Basing our work on the theoretical and methodological perspective of Sylvain Auroux (1989; 1992; 2008) we establish a method of defining the causes that led these authors to propose a specific method for language instruction as well as the effects stemming from this method to shed light on the theoretical and philosophical foundations common to them, by means of a broad horizon of retrospection of knowledge, as evidenced by the co-presence of significant authors of that time. Finally, because it is related to the investigation of the construction of knowledge regarding language and language instruction through an analysis of the causes of changes in knowledge, considering dimensions (object, time, space parameters external to the text, and the interference of interpreters) and their relationship (Auroux, 2008), this work is inscribed in the History of Linguistic Ideas